Rayleigh Wave Propagation at Viscous Liquid/Micropolar Micro-stretch Elastic Solid - Somaiah, K.; Kumar, A. Ravi (Communications in Mathematics and Applications, 2023)
In this article, the governing equations of a homogeneous, isotropic micropolar microstretch elastic solid for xz-plane are considered and solved for surface wave propagation. Two types of frequency equations for Rayleigh waves are derived, in which one is along the free surface of micropolar micro-stretch elastic solid half space and another is at viscous liquid/micropolar micro-stretch solid interface. These are dispersive in nature. In the study of some particular cases, we observed that four types of Rayleigh waves are propagate, out of these, two waves are at free surface of generalized micropolar solid and micro-stretch solid and another two types of waves are at interface of viscous liquid/non-microstretch solid. In these four waves, three Rayleigh waves are dependent on solid density and one of them is non-dispersive in nature. Numerical example is considered for a particular solid and viscous liquid layer and the frequency curves are drawn and discussed with the help of MATLAB programme.
Keywords: Micropolar micro-stretch elasticity; Viscous liquid layer; Rayleigh waves; Frequency equation